Determination of vestibular function in children with purulent otitis media - Lozova, Iuliia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
The aim of the study is to assess the vestibular function of children with acute purulent otitis media by computer static stabilometry compared with typically developed peers. Materials and methods. In the course of the study 52 children aged 4 to 7 were examined by static stabilometry on the device «MPFI Stabilograph 1» (Kharkiv, Ukraine). 22 of them were diagnosed with purulent otitis media and their 30 peers were found to be practically healthy. Indicators of variations and forms of pressure center distribution, spectral-correlation indicators of stabilograms, as well as integral indicators of stability (length, velocity and angle of postural oscillations) and quality of equilibrium function in two sensory states (open and closed eyes) calculated in StabiliS software were taken into account. Results. Purulent otitis media causes posterior displacement of absolute coordinates of the pressure center. In the state with closed eyes, children with purulent otitis differ from their healthy peers in 14 of 24 stabilometric parameters, including stabilogram length, speed, angle and amplitude of oscillations, inferior to them in the balance. Children with purulent otitis media are more sensitive to the visual canal of postural control than their peers. Involvement of visual afferents in postural control significantly improves balance in children with purulent otitis by reducing deviations, postural fluctuations, which is reflected in the probable changes of 9 out of 24 stabilometric parameters compared to control. Conclusion. In preschool age, purulent otitis media leads to latent vestibular dysfunction, which is manifested by a violation of the stability of the vertical posture with the closed eyes and is compensated by visual-vestibular-proprioceptive integration in postural control.